Trehalose prevents cadmium-induced hepatotoxicity by blocking Nrf2 pathway, restoring autophagy and inhibiting apoptosis - Gong, Zhong-Gui; Wang, Xin-Yu; Wang, Jun-Hong; Fan, Rui-Feng; Wang, Lin (Journal of inorganic biochemistry, 2019)
Cadmium (Cd) is a ubiquitously distributed environmental pollutant that is highly toxic to liver. Trehalose (Tr), a novel autophagy activator, has been shown to exert cytoprotective effect in numerous pathological processes. However, it is yet to be established whether Tr affords protection against Cd-induced hepatotoxicity. Here, we aimed to investigate the protective effect of Tr on Cd-induced hepatic injury in rats. First, Cd-elevated serum hepatic enzymes and liver pathological changes were significantly ameliorated by Tr treatment. Also, Tr remarkably improved Cd-mediated oxidative stress and antioxidant status in serum, indicating its anti-oxidant action for the whole body. Cd-stimulated nuclear factor erythroid 2-related factor 2 (Nrf2) nuclear translocation and subsequent elevated expression of Nrf2-downstream targets in rat liver were significantly inhibited by Tr treatment. Simultaneously, Cd-elevated protein levels of hepatic antioxidant enzymes were markedly downregulated by administration with Tr. Moreover, Cd-induced autophagy inhibition in liver tissues was noticeably restored by Tr, evidenced by immunohistochemical analysis and immunoblot assays. Additionally, Tr treatment significantly mitigated Cd-induced apoptosis in hepatic tissues via inhibiting caspase-dependent apoptotic pathway. In conclusion, these observations demonstrate that Tr treatment alleviates Cd-induced liver injury by blocking Nrf2 pathway, restoring autophagy and inhibiting apoptosis. Cadmium-induced oxidative stress is intimately related to the activation of nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway (nuclear translocation), which contributes to autophagy inhibition and apoptosis in rat liver. Trehalose alleviates cadmium-induced oxidative stress and Nrf2 pathway activation, thereby restoring autophagy and inhibiting apoptosis to prevent cadmium-induced hepatotoxicity. [Display omitted] •Trehalose protects against cadmium-induced liver injury via its anti-oxidative activity.•Nrf2 is the abbreviation of nuclear factor erythroid 2-related factor 2.•Trehalose inhibits cadmium-activated Nrf2 signaling pathway in rat liver•Trehalose attenuates cadmium-induced apoptosis in rat liver.•Trehalose restores cadmium-induced autophagy inhibition in rat liver.